Compensation of Voltage Sag and Swell Using SMES Based Dynamic Voltage Restorer - N. A. Jayakumar; R. Devarajan (Journal of Power Electronics and Devices, 2019)
Conducting Magnetic Energy Storage (SMES) is portrayed by profoundly proficient vitality storage. It has fast reaction and power controllability and is relied upon to add to brilliant intensity of the power grid. SMES innovation can possibly bring genuine power storage trademark and furthermore high power and vitality thickness for momentary reaction. This normal for SMES used to shield buyers from the network voltage variances like sag, swell and interference. This paper examinations the activity guideline of the SMES based DVR and its structure depends on basic PI control technique to repay voltage droops, swell and intrusion. Utilizing MATLAB/SIMULINK, the models of the SMES based DVR is set up, and the re-enactment tests are performed to assess the grid disturbances.